Optimisation of Design and Operation Parameters for Multicomponent Separation via Improved Lewis-Matheson Method - Ching Tiong, C.; Nandong, Jobrun (De Gruyter, 2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston 2017. Distillation is the most commonly used separation and purification technique in the chemical and allied industries despite that it has been known as the most energy-consuming unit in process industry. The need to reduce this energy consumption has become one of the important focuses in the efficient design and optimization of distillation processes. In the present work, we propose an improved Lewis-Matheson stage-by-stage procedure by incorporating the Fenske equation to enhance the estimation of the non-key component distributions, and thus avoiding infeasible solutions to the stage-by-stage system of equations of mass and energy balances. A modified theta method is also included in the design procedure to satisfy the feed stage matching criteria which help reduces the computational time while increasing the accuracy of feed composition matching. By using the proposed modified Lewis-Matheson method, an optimization is conducted in Matlab environment where the problem formulation takes into account both sets of design and operating parameters with specified product purity as the constraint. The objective function of the optimization is to minimize the Total Annualized Cost (TAC), which includes both capital and operating costs. The effectiveness of the proposed design procedure is demonstrated using an industrial-scale natural gas liquids (NGLs) depropanizer fractionation unit.